Ethical guidelines for publishing in the journal of cachexia, sarcopenia and muscle: update 2017. Issue 6 (3rd November 2017) - von Haehling, Stephan; Morley, John E.; Coats, Andrew J.S.; Anker, Stefan D.
Abstract: This article details an updated version of the principles of ethical authorship and publishing in the Journal of Cachexia, Sarcopenia and Muscle (JCSM). At the time of submission to JCSM, the corresponding author, on behalf of all co‐authors, needs to certify adherence to these principles. The principles are as follows: All authors listed on a manuscript considered for publication have approved its submission and (if accepted) publication as provided to JCSM. No person who has a right to be recognized as author has been omitted from the list of authors on the submitted manuscript. Each author has made a material and independent contribution to the work submitted for publication. The submitted work is original and is neither under consideration elsewhere nor that it has been published previously in whole or in part other than in abstract form. All authors certify that the work is original and does not contain excessive overlap with prior or contemporaneous publication elsewhere, and where the publication reports on cohorts, trials, or data that have been reported on before these other publications must be referenced. All original research work has been approved by the relevant bodies such as institutional review boards or ethics committees. All conflicts of interest, financial or otherwise, that may affect the authors' ability to present data objectively, and relevant sources of funding have been duly declared in the manuscript. The manuscript in its published form will be maintained on the servers of JCSM as a valid publication only as long as all statements in the guidelines on ethical publishing remain true. If any of the aforementioned statements ceases to be true, the authors have a duty to notify the Editors of JCSM as soon as possible so that the available information regarding the published article can be updated and/or the manuscript can be withdrawn.